2009
DOI: 10.1179/147842208x320306
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of rust on microalloyed rail steel exposed to coastal location in India

Abstract: The rusts on the gauge face and non-gauge face of two rail steels (traditional C-Mn and novel CuMo rail steel) were characterised after two years of service to corelate with an apparent visual observation of a lower corrosion rate in the case of the Cu-Mo rails. Rust samples were characterised by X-ray diffraction, Fourier transform infrared spectroscopy and Mö ssbauer spectroscopy. X-ray diffraction patterns showed diffuse peaks indicating poorly crystallised rust phases, while the phases identified by the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It has been found that rust composition highly depended on different microalloying elements, and novel rail steels exhibited compact thus more protective rust films. Similar effect for corrosion products has also been found on a newly developed U76CrRE rail steel (Wang et al 2013) and novel Cu-Mo rail steel (Panda et al 2009c). Corrosion of novel U68CuCr steel has also been compared with traditional U75V steel, indicating a better corrosion resistance with alloyed Cu and Cr, likely to be ascribed to change on microstructure instead of variation of corrosion products (Ren et al 2013).…”
Section: Development Of Novel Rail Track Steelssupporting
confidence: 61%
“…It has been found that rust composition highly depended on different microalloying elements, and novel rail steels exhibited compact thus more protective rust films. Similar effect for corrosion products has also been found on a newly developed U76CrRE rail steel (Wang et al 2013) and novel Cu-Mo rail steel (Panda et al 2009c). Corrosion of novel U68CuCr steel has also been compared with traditional U75V steel, indicating a better corrosion resistance with alloyed Cu and Cr, likely to be ascribed to change on microstructure instead of variation of corrosion products (Ren et al 2013).…”
Section: Development Of Novel Rail Track Steelssupporting
confidence: 61%
“…Nonetheless, the average COF for the microalloyed rail steel samples is slightly lower than that of the R260 rail steel samples for all tested conditions. This is because microalloyed rail steel is more corrosion resistant than R260 rail steel [17][18] and less prone to the formation of hematite on the surface of the rail head. It can thus be concluded that reduced oxidation of microalloyed rail steel leads to a decrease in the coefficient of friction.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, little research has been published to date on the friction behavior of microalloyed rail steels. Panda et al [17][18] analysed the nature of the oxide generated on microalloyed steel rails compared to traditional C-Mn steel rails, finding that microalloyed rail steels have a greater corrosion resistance than commonly used C-Mn rail steels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Panda et al. 4 analysed the nature of oxides generated in Cu and Mo microalloyed rail steels after a service period of two years compared to the traditional C–Mn rail steels. The results showed a lower corrosion rate in the case of the Cu–Mo rail steels.…”
Section: Introductionmentioning
confidence: 99%